An alternative construction of the Hermitian unital 2‐(28, 4, 1) design. Issue 12 (26th September 2022) - Inoue, Koichi
Abstract: In this paper, we give an alternative construction of the Hermitian unital 2‐(28, 4, 1) design in such a way that it is constructed on the isotropic vectors in a unitary geometry of dimension 3 over the field F 4 F_4 . As a corollary, we can construct a unique 3‐(10, 4, 1) design (namely, the Witt system W 10 W_10 ).